Does oral ingestion of piper sarmentosum cause toxicity in experimental animals? - Mohd Zainudi, Maizura; Zakaria, Zaiton; Megat Mohd Nordin, Nor Anita; Othman, Faizah (Hindawi Publishing Corporation, 2013)
The prevalence of diabetes mellitus has reached epidemic proportion in Malaysia and worldwide. Scientific studies have shown that herbal plant Piper sarmentosum exhibits an antidiabetic property. Despite the extensive usage and studies of this herb as alternative medicine, there is paucity of the literature on the safety information of this plant. Thus, the present study aimed to observe the subacute toxic effects of Piper sarmentosum aqueous extract (PSAE) on the haematological profile, liver, and kidney in rats. The extract was administered by oral gavage to 6 male and female Sprague Dawley rats in daily dose of 50 mg/kg, 300 mg/kg, and 2000 mg/kg for 28 consecutive days. The control group received normal saline. General behavior of the rats, adverse effects, and mortality were observed for 28 days. The haematological and biochemical parameters were determined at baseline and after the treatment. PSAE did not show abnormality on the body weight and gross observation of internal organs. The haematological, biochemical and histopathological profiles showed minimal changes and variation within normal clinical range except for significant increase in serum potassium level that suggests the need of regular monitoring. Nevertheless, these findings suggested that PSAE up to 2000 mg/kg/day did not show subacute toxicity in Sprague Dawley rats.